The Effect of a Functional Strength Training Intervention on Movement Quality and Physical Fitness in Adolescents. Issue 1 (February 2022) - Liao, Ting; Duhig, Steven J; Du, Geng; Luo, Bingting; Wang, Yong Tai
This study compared a 12 week Functional Strength Training (FST) program on functional movement and physical performance to typical physical education (PE) classes for middle school (MS) and high school (HS) students. We randomly assigned 266 participants ( M age = 14.35, SD = 0.57 years; M height = 164.82, SD = 6.13 cm; M mass = 55.09, SD = 12.19 kg; M BMI = 20.11, SD = 3.54 kg/m 2 ) into an FST or control group. The FST group trained in flexibility and stability, functional movement patterns, and health-related functional strength. The control group continued regular physical education (PE) classes. Each group trained three-times/week in 45 minute sessions for 12 weeks. Outcome measures included the Functional Movement Screen protocol and seven physical performance tests, assessed every four weeks over a 12 week period. We employed a mixed model ANOVA with Bonferroni post-hoc tests to examine differences between and within groups. Compared to the control group, the FST group significantly ( p < 0.01) improved Functional Movement Screen total scores (25.7%), curl-ups (70.4%), pull-ups (281.6%), and flexibility (83.6%). We suggest including the FST program in the MS and HS PE curriculum.